2015
DOI: 10.1016/j.mito.2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Differences in mitochondrial function in homogenated samples from healthy and epileptic specific brain tissues revealed by high-resolution respirometry

Abstract: Mitochondrial dysfunction and oxidative stress are strongly implicated in neurodegenerative diseases and epilepsy. Strikingly, neurodegenerative diseases show regional specificity in vulnerability and follow distinct patterns of neuronal loss. A challenge is to understand, why mitochondria fail in particular brain regions under specific pathological conditions. A potential explanation could be provided by regional or cellular specificity of mitochondrial function. We applied high-resolution respirometry to ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 29 publications
3
51
0
Order By: Relevance
“…Furthermore, the absolute OCR of striatal mitochondria, when provided succinate, was larger than mitochondria of the cerebral cortex, which was not the case when using pyruvate and malate as respiratory substrates. Several recent studies have reported elevations in both coupled and uncoupled OCRs of striatal mitochondria when provided succinate as substrate, which is in line with our results (Burtscher et al, ; Pandya et al, ; Subramaniam, Vergnes, Franich, Reue, & Chesselet, ). A general hypothesis on the pathogenesis of Huntington’s disease, a disease primarily affecting the striatum, is that the mitochondria of the striatum are more sensitive to metabolic insults and therefore more susceptible to neurodegeneration (Browne & Beal, ; Damiano, Galvan, Deglon, & Brouillet, ; Mochel & Haller, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, the absolute OCR of striatal mitochondria, when provided succinate, was larger than mitochondria of the cerebral cortex, which was not the case when using pyruvate and malate as respiratory substrates. Several recent studies have reported elevations in both coupled and uncoupled OCRs of striatal mitochondria when provided succinate as substrate, which is in line with our results (Burtscher et al, ; Pandya et al, ; Subramaniam, Vergnes, Franich, Reue, & Chesselet, ). A general hypothesis on the pathogenesis of Huntington’s disease, a disease primarily affecting the striatum, is that the mitochondria of the striatum are more sensitive to metabolic insults and therefore more susceptible to neurodegeneration (Browne & Beal, ; Damiano, Galvan, Deglon, & Brouillet, ; Mochel & Haller, ).…”
Section: Discussionsupporting
confidence: 93%
“…Compared to the literature, these values signify well-functioning mitochondria, validating the quality of our preparation (Burtscher, Zangrandi, Schwarzer, & Gnaiger, 2015;Cardoso, Santos, Seica, & Moreira, 2010;Czerniczyniec et al, 2015;Dagani et al, 1988;Lai et al, 1977;Sauerbeck et al, 2011;Sims, 1990;Varela, Schwartz, & Horvath, 2016). We observed that hippocampal mitochondria exhibited a larger proton leak, with both substrate conditions, resulting in reduced RCR values for this region.…”
Section: Mitochondrial Isolation and Functionsupporting
confidence: 84%
“…No significant changes between HDEMCs and controls were detected in these parameters (Fig 2A). In addition complex I and complex II activity were examined in the limited amount of tissue sample, by accepting the restriction that complex II activity could be determined in an uncoupled state only, as it was described before [22, 29]. Neither complex I activity nor complex II activity showed significant changes between the HDEMCs and the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, 3-NP inhibits the succinate dehydrogenase (SDH, or mitochondrial complex II) catalytic site; blocking the electron transport chain and the Krebs cycle, decreasing ATP synthesis and promoting reactive oxygen species (ROS) formation, thus fomenting mitochondrial dysfunction [7] and neuronal death [8], [9].…”
Section: Introductionmentioning
confidence: 99%